Multi-drug-loaded gastric-floating microcapsules - Tan, Melvin Jun Wei (2014)
Recent advances in floating drug delivery systems (FDDS) have been developed to increase drug bioavailability and reduce patients’ dosing frequency and pill burden, by means of an effective sustained release. Nevertheless, with most hydrophobic drugs unable to achieve complete release within the gastrointestinal (GI) residence period (10 hours for FDDS), an understanding of how to promote drug release in such systems is essential. This study explores modified gastro-retentive polymeric floating microcapsule fabricating processes that simultaneously release metformin hydrochloride, a hydrophilic drug, and fenofibrate, a hydrophobic drug, in a controlled manner, seeking to promote the release rate of the hydrophobic drug. A comparable study using a solvent evaporation method to create multi-drug gastric floating microcapsules achieved 86% metformin hydrochloride release and only 20% fenofibrate release within 10 hours. The first process developed in this study using a spray-coating technique could achieve 87% to 100% metformin hydrochloride release within 10 hours and 100% fenofibrate release between 1 to 10 hours by parameter variation. The second process created bi-layer gastric floating microspheres in a single-step process achieving 100% fenofibrate release within 10 hours. The study also explored a fabrication technique where spray-coated gastric floating microcapsules were capable of producing loading dose and maintenance dose.